Consideration of autonomous (automated) weapons: challenges to the Just War Theory in the Future of Warfare [Thesis] - Toktarova, Gulden (Nazarbayev University School of Sciences and Humanities, 2019)
The incredibly quick development of smart technologies in the civil sector and in the sphere of war equipment, in particular, increases the public fear of future overrun by killer robots. Despite the actual absence of fully autonomous weaponry, the international community stands in opposition towards the development of weaponry that potentially will be capable of detecting and eliminating human targets without human intervention changing the nature of killing in war. With the autonomous weaponry issue and the concept of moral judgement in the case of killing in war, future technology seems to challenge the key moral principles of Just War Theory that condition the moral frames of the different stages of war. These principles are differentiation between combatants and non-combatants, reciprocal risk of death and the responsibility for the wrongdoings committed during war. The challenges that Just War Theory faces due to the existence of smart killing technology are considered within the frame of automated weaponry instead of fully autonomous. This paper suggest the alternative conceptual clarification of the smart war technologies and sees full autonomy of the technologies as impossible in the nearest future. Our approach entails dealing with the more probable to exist weaponry - automated weaponry with lethal pre-programed activated autonomy or capable of detecting and eliminating the target based on the software without human intervention after its activation (AW). The very definition of the AW shows the need for a detailed and properly checked development of weapons technology. AWs also require the application of a wide spectrum of characteristics of the legitimate and illegitimate targets including a variety of situations and environments with respect to the moral principles of war and other International Law requirements. This important notice and other essential principles of Just War Theory are uncovered in this thesis to show the possibility of the moral use of AWs within modern warfare.
Рассмотрение автономного оружия: вызов по отношению к теории справедливой войны в рамках будущего войны
Keywords: Autonomous Weapons; Autonomous Robots; Just War Theory; Jus in bello; Moral rules; Automated weapons; Artificial intelligence; Research Subject Categories::SOCIAL SCIENCES